Remedial teachers’ needs for developing new basic numeracy teaching aids: a needs analysis - Low, Weng Sheng; Mohd Mokhtar Tahar,; Siti Mistima Maat,; Mohd Syazwan Zainal, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Appropriate teaching aids can assist remedial pupils in mastering basic numeracy skills effectively. However, issues persist of remedial pupils struggling to grasp basic numeracy skills, potentially due to the lack of suitable teaching aids tailored for Malaysia’s Special Remedial Programme. Thus, this quantitative study aimed to identify remedial teachers' needs for developing new basic numeracy teaching aids in the Special Remedial Programme. This study adapted McKillip's Discrepancy Model to guide the needs analysis. A quantitative survey methodology was used with 143 remedial teachers respondents in Melaka state, Malaysia. A validated questionnaire measured the levels and discrepancies in remedial teachers’ utilisation, perceptions, constraints, and skills regarding proposed basic numeracy teaching aids by the Ministry of Education Malaysia. Descriptive statistics were calculated. Findings showed moderate utilisation, high positive perception, moderate constraints, and high skills levels in using existing basic numeracy teaching aids. Discrepancies were identified in each construct, indicating the need for improvements tailored for better remedial learning. The results suggest modifying and developing new basic numeracy teaching aids that meet remedial pupils’ learning characteristics, fostering their creative thinking, facilitating self-directed learning activities, improving time efficiency in teaching and learning mathematics, providing various customisable teaching aid templates that are easy to reproduce with affordable everyday materials, and developing user-friendly technology teaching aids. Addressing these needs can enhance remedial teaching practices and pupils’ numeracy achievement. This study provides an important initial evidence base for designing and developing appropriate basic numeracy teaching aids based on remedial teachers’ current needs.